Experiences and well-being of Ugandan teachers working in a refugee settlement during the COVID-19 school closure - Saarivuori, Tea (2022)
The aim of this study was to find out how the Ugandan COVID-19 school closure affected the well-being of Ugandan teachers working in a refugee settlement. Teacher well-being has been recognised as a major driver of quality education and it has received a lot of attention from researchers, but the well-being of teachers working in low-resource, crisis and conflict-affected settings is an under-researched topic, and there is little research on teaching during the COVID-19 school closures in contexts where online learning was not feasible. This study concentrated on the challenges, successes, and stressors that the Ugandan teachers working in a refugee settlement experienced during the first year of the school closure, from March 2020 to March 2021, and whether their job motivation changed during that time.